PEMANFAATAN LIMBAH BUNGA JANTAN KLUWIH SEBAGAI LARVASIDA NYAMUK Aedes Aegypti - Ade Heri Mulyati; Diana Widiastuti; Putry Sri Ratih (Universitas Pakuan, 2014)
The breadfruit tree Artocarpus altilis species is a species that is often used fruit as a food source , while the stems and roots of this plant can be used as a medicinal plant. Around the area of Sukabumi, west Java people use the bread fruit tree flowers as a insect repellent. The purpose of this study is to determine the potential of breadfruit tree stamens extracts as larvicides against Aedes aegypti mosquito larvae and determine the optimum concentration of extract of stamens breadfruit tree which can be used effectively as Aedes aegypti mosquito larvicides. Determine larvicidal activity of stamens breadfruit tree (Artocarpus altilis) includes : sample preparation and phytochemical test , sextraction , larvicidal test , toxicity testing and data processing . Comparison test was done to compared the activity of the male flower extracts as larvicides with breadfruit tree abate powder against mosquito larvae , as well as the toxicity of the statistical test using the LC50.Phytochemical test results positive breadfruit tree botanicals stamens contain tannins , saponins , and triterpenoids . Water content in the crude drug obtained 12.04 % . Breadfruit tree extract of stamens is not harmful to humans . This study getting the LC50 of 0.25 % at phase n - butanol extract , and 1 % in the water phase extract.Key words : Waste, Breadfruit, Aedes aegypti, Artocarpus altilis